Gambaran Harapan Orang Tua (Single Parent) Terhadap Anak - Firyal Dinar Alysia; Kurniati Zainuddin; Muhrajan Piara (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Hope is a mental condition that combines an individual's ability to create strategies to achieve goals, a form of motivation to execute those strategies, and positive optimism about expected outcomes for the future. This study aims to understand the overview of single parents' hopes for their children and the dynamics of how these hopes are formed. The research is a qualitative study with a phenomenological approach. The subjects of this study are three single parents: a single mother due to the death of a spouse, a single mother due to divorce, and a single father due to the death of a spouse. Data was collected through interviews, resulting in interview transcripts and voice recording documentation. The coded data was then analyzed for interpretative consistency between the subjects and the researcher. The study found that single parents' hopes include aspirations in education, health, spiritual life, personality and independence, success, and social and relational development. The dynamics that shape these hopes include changes, the emotional state of the subjects, efforts and perceptions, self-acceptance, commitment, challenges, support, and motivation.